First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Inland waterway traffic noise prediction model: a comparison - B. L. Dai; N. Sheng; J. Huang; F. H. Mu; X. Chen; T. Li; J. M. Xu; Y. L. He (International Journal of Environmental Science and Technology, 2024)

Efficient denitrification by a salt-tolerant aerobic compound bacteria agent AHM M3: optimizing composition and reduction conditions - H. Ma; Y. Liu; X. Mu; J. Song; X. Su; Y. Wu; R. Han (International Journal of Environmental Science and Technology, 2023)

Photoperiod drives cessation of wood formation in northern conifers - Wenhuan Mu; Xiuchen Wu; J. Julio Camarero; Yongshuo H. Fu; Jianguo Huang; Xiaoyan Li; Deliang Chen (Global Ecology and Biogeography, 2023)
Aims Shifts in xylem phenology directly determine the forest capacity for carbon sequestration. However, a systematic understanding of the spatial patterns and the underpinning drivers in determining the cessation of wood formation ( C cw ) is lacking at a pan‐continental scale. Here, we addressed this knowledge gap by compiling a new dataset of multiple xylem phenology timings for northern conifers. Locations Sixty‐two study sites, Northern Hemisphere (25–55° N). Time period 2003–2018 (16 years). Taxa Thirty‐three conifer species. Methods A generalized additive model was fitted to characterize the latitudinal pattern in C cw . Structural equation modelling and a linear mixed‐effects model were applied to determine the main drivers underlying the latitudinal pattern in C cw . Results The C cw followed a flat S‐shaped pattern with increasing latitude. Photoperiod was the dominant determinant of the latitudinal pattern of C cw , and a longer photoperiod was associated with an earlier C cw . Both mean growing‐season temperature and total growing‐season precipitation exhibited significantly positive relationships to the cessation of cell elongation and thus the C cw across all study sites. In arid regions, the pre‐growing‐season temperature had a significantly negative effect on C cw . In humid regions, C cw was positively affected by the mean growing‐season temperature. The onset of wood formation showed significantly positive coupling with C cw at arid sites but not at humid sites. Early successional species were sensitive to hydrothermal variations during the pre‐growing season. Main conclusions We reveal the dominant role of photoperiod in determining the cessation of wood formation for northern conifers and highlight differentiated interactive effects between photoperiod and seasonal climatic factors and the preceding xylem phenophases in determining C cw among ecoregions and tree species. These insights provide evidence to reduce uncertainty in prediction of the forest carbon uptake potential and the consequent biophysical feedbacks of northern forests.

Biophysical Reviews special issue call: quantitative methods to decipher cellular heterogeneity — from single-cell to spatial omic methods - Joshua W. K. Ho; Xi Chen; Mu He; Yuanhua Huang; Jessica C. Mar; David J. H. Shih; Angela R. Wu (Biophysical Reviews, 2022)

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

WormBot, an open-source robotics platform for survival and behavior analysis in C. elegans - Jason N. Pitt; Nolan L. Strait; Elena M. Vayndorf; Benjamin W. Blue; Christina H. Tran; Brendon E. M. Davis; Karen Huang; Brock J. Johnson; Keong Mu Lim; Sophie Liu; Arash Nikjoo; Anuj Vaid; et al. (GeroScience, 2019)

Development of an inland waterway traffic noise prediction model considering water surface adsorption and embankment shielding influences - B. L. Dai; N. Sheng; Y. L. He; F. H. Mu; J. M. Xu; A. F. Zhu (International Journal of Environmental Science and Technology, 2019)

Clinical characteristics of 154 patients suspected of having Ebola virus disease in the Ebola holding center of Jui Government Hospital in Sierra Leone during the 2014 Ebola outbreak - T. Yan; J. Mu; E. Qin; Y. Wang; L. Liu; D. Wu; H. Jia; Z. Li; T. Guo; X. Wang; Y. Qin; Y. Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

A novel microbead-based microfluidic device for rapid bacterial identification and antibiotic susceptibility testing - J. He; X. Mu; Z. Guo; H. Hao; C. Zhang; Z. Zhao; Q. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Apoptosis repressor with caspase recruitment domain is regulated by MAPK/PI3K and confers drug resistance and survival advantage to AML - P. Y. Mak; D. H. Mak; H. Mu; Y. Shi; P. Ruvolo; V. Ruvolo; R. Jacamo; J. K. Burks; W. Wei; X. Huang; S. M. Kornblau; M. Andreeff; et al. (Apoptosis, 2014)

Satellite‐derived estimates of forest leaf area index in southwest Western Australia are not tightly coupled to interannual variations in rainfall: implications for groundwater decline in a drying climate - Keith R. J. Smettem; Richard H. Waring; John N. Callow; Melissa Wilson; Qiaozhen Mu (Global Change Biology, 2013)
There is increasing concern that widespread forest decline could occur in regions of the world where droughts are predicted to increase in frequency and severity as a result of climate change. The average annual leaf area index ( LAI ) is an indicator of canopy cover and the difference between the annual maximum and minimum LAI is an indicator of annual leaf turnover. In this study, we analyzed satellite‐derived estimates of monthly LAI across forested coastal catchments of southwest Western Australia over a 12 year period (2000–2011) that included the driest year on record for the last 60 years. We observed that over the 12 year study period, the spatial pattern of average annual satellite‐derived LAI values was linearly related to mean annual rainfall. However, interannual changes to LAI in response to changes in annual rainfall were far less than expected from the long‐term LAI ‐rainfall trend. This buffered response was investigated using a physiological growth model and attributed to availability of deep soil moisture and/or groundwater storage. The maintenance of high LAI s may be linked to a long‐term decline in areal average underground water storage and diminished summer flows, with an emerging trend toward more ephemeral flow regimes.

Expression profiles of seven channel catfish antimicrobial peptides in response to Edwardsiella ictaluri infection - J W Pridgeon; X Mu; P H Klesius (Journal of Fish Diseases, 2012)
Using quantitative polymerase chain reaction (QPCR), the relative transcriptional levels of seven channel catfish antimicrobial peptide (AMP) genes (NK‐lysin type 1, NK‐lysin type 2, NK‐lysin type 3, bactericidal permeability‐increasing protein, cathepsin D, hepcidin and liver‐expressed AMP 2) in response to Edwardsiella ictaluri infection were determined. None of the AMP genes tested was significantly upregulated at 2 h post‐infection. Hepcidin was the only one that was significantly ( P P E. ictaluri , all lethal doses were able to induce significant ( P In vitro growth studies revealed that the presence of synthetic hepcidin peptide at a concentration of 16 μ m or higher significantly inhibited the cell proliferation of E. ictaluri . Taken together, our results suggest that hepcidin might play an important role in the channel catfish defence against E. ictaluri infection.

The chromosomal localization, expression pattern and polymorphism analysis of porcine FSCN1 gene differently expressed from LongSAGE library - Zh. L. Tang; X. J. Zhang; Sh. L. Yang; Y. L. Mu; W. T. Cui; H. Ao; K. Li (Molecular Biology Reports, 2010)

Evaluation of Combined Toxicity of Phenols and Lead to Photobacterium phosphoreum and Quantitative Structure–Activity Relationships - L. M. Su; Y. H. Zhao; X. Yuan; C. F. Mu; N. Wang; J. C. Yan (Bulletin of Environmental Contamination and Toxicology, 2010)

Partial molecular cloning, characterization, and analysis of the subcellular localization and expression patterns of the porcine OTUB1 gene - T. L. Shan; Z. L. Tang; D. Z. Guo; S. L. Yang; Y. L. Mu; Y. H. Ma; W. J. Guan; K. Li (Molecular Biology Reports, 2009)

100 years of Sediment History of Heavy Metals in Daya Bay, China - J. Z. Du; H. D. Mu; H. Q. Song; S. P. Yan; Y. J. Gu; J. Zhang (Water, Air, & Soil Pollution, 2008)

Comparison of Particle Image Velocimetry and Laser Doppler Anemometry Measurements in Turbulent Fluid Flow - M. P. Wernet; A. Subramanian; H. Mu; J. R. Kadambi (Annals of Biomedical Engineering, 2000)